OsGRETCHENHAGEN3-2 modulates rice seed storability via accumulation of abscisic acid and protective substances. Issue 1 (11th February 2021) - Yuan, Zhiyang; Fan, Kai; Wang, Yuntong; Tian, Li; Zhang, Chaopu; Sun, Wenqiang; He, Hanzi; Yu, Sibin
Abstract : Inactivation of indole-3-acetic acid by an IAA-amido synthetase inhibits abscisic acid signaling and reduces protective proteins, leading to poor seed storability in rice. Abstract: Seed storability largely determines the vigor of seeds during storage and is significant in agriculture and ecology. However, the underlying genetic basis remains unclear. In the present study, we report the cloning and characterization of the rice ( Oryza sativa ) indole-3-acetic acid (IAA)-amido synthetase gene GRETCHEN HAGEN3-2 ( OsGH3-2 ) associated with seed storability. OsGH3-2 was identified by performing a genome-wide association study in rice germplasms with linkage mapping in chromosome substitution segment lines, contributing to the wide variation of seed viability in the populations after long periods of storage and artificial ageing. OsGH3-2 was dominantly expressed in the developing seeds and catalyzed IAA conjugation to amino acids, forming inactive auxin. Transgenic overexpression, knockout, and knockdown experiments demonstrated that OsGH3-2 affected seed storability by regulating the accumulation level of abscisic acid (ABA). Overexpression of OsGH3-2 significantly decreased seed storability, while knockout or knockdown of the gene enhanced seed storability compared with the wild-type. OsGH3-2 acted as a negative regulator of seed storability by modulating many genes related to the ABA pathway and probably subsequently late embryogenesis-abundant proteins at the transcription level. These findings shed light on the molecular mechanisms underlying seed storability and will facilitate the improvement of seed vigor by genomic breeding and gene-editing approaches in rice.